I, Steve Steve Jobs in his own words - Beahm, George (Richmond (Vic.) Hardie Grant Books, 2011)
Fortune magazine proclaimed Jobs 'the CEO of the decade'. Harvard Business Review called him 'the world's best-performing CEO'. And the Wall Street Journal praised him as a 'Person of the Decade'. The longtime CEO of Apple, Inc., which he co-founded in 1976, Steve Jobs stepped down from that role in August 2011, bringing an end to one of the greatest, most transformative business careers in history. Over the years
1
Keywords: Jobs, Steve, -- 1955-2011 -- Quotations; Jobs, Steve, -- 1955-2011